RELIGIUSITAS MEDIA MASSA DALAM PERSPEKTIF TEOANTROPOSENTRIS ISLAM - Mujiati, Nanik; Yunus, Moh. (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This article examines about Islamic Theoantropocentric, a new paradigm of integration between the source of knowledge from Allah in the form of the Qur’an and human science. Islamic theoantroposentric phenomena that exist in the mass media space or called mass media religiosity. This form of religiosity is in the form of morals which is sourced from the revelation of Allah contained in the Qur’an and hadith. While the mass media itself is in the form of human knowledge such as print media, electronics and new media. The existence of integration between mass media and religion is complementary and become a unified whole. The use of mass media must be accompanied by the morals or ethics of the mass media. Mass media as public media must present religious content or that does not deviate from the teachings of Islam to meet the needs of the audience, especially Muslims themselves. So that the mass media with morals can create good communication and bring benefit to mankind, even the mass media can be a means of minimizing conflict.Keywords: Theoantropocentric, Islamic, and Mass Media.